Winter corticosterone and body condition predict breeding investment in a nonmigratory bird. (2nd August 2019) - Montreuil-Spencer, Chloé; Schoenemann, Kelsey; Lendvai, Ádám Z; Bonier, Frances
Abstract: Reproduction is an energetically demanding life history stage that requires costly physiological and behavioral changes, yet some individuals will invest more into reproduction and breed more successfully than others. To understand variation in reproductive investment, previous studies have evaluated factors during breeding, but conditions outside of this life history stage may also play a role. Using a free-ranging population of black-capped chickadees ( Poecile atricapillus ), we assessed the repeatability of plastic traits relating to energetic condition (circulating initial corticosterone concentrations and body condition) during the nonbreeding season and evaluated whether these traits predicted reproductive investment in the subsequent breeding season. We found that initial corticosterone concentrations and an index of body condition, but not fat score, were moderately repeatable over a 1-week period in winter. This trait repeatability supports the interpretation that among-individual variation in these phenotypic traits could reflect an intrinsic strategy to cope with challenging conditions across life history stages. We found that females with larger fat reserves during winter laid eggs sooner and tended to spend more time incubating their eggs and feeding their offspring. In contrast, we found that females with higher residual body mass delayed breeding, after controlling for the relationship between fat score and timing of breeding. Additionally, females with higher initial corticosterone in winter laid lighter eggs. Our findings suggest that conditions experienced outside of the breeding season may be important factors explaining variation in reproductive investment. Abstract : Energetic challenges confronting individuals during one season may influence how they invest resources in a subsequent season. Black-capped chickadees confronting greater challenges in winter or having lower inherent quality invested less energetic resources into breeding during the following spring. Additionally, corticosterone levels and an index of body condition were repeatable, suggesting that among-individual variation in these traits could reflect consistent differences in individuals' strategies or abilities to cope with challenges year-round.